The optimization of avocado-seed-starch-based degradable plastic synthesis with a polylactic acid (PLA) blend using response surface methodology (RSM) - Dewi, Rozanna; Sylvia, Novi; Zulnazri, Zulnazri; Fithra, Herman; Riza, Medyan; Siregar, Januar Parlaungan; Cionita, Tezara; Fitriyana, Deni Fajar; Anis, Samsudin (MDPI, 2024)
This research improves the strength of plastic using avocado seed starch and PLA. The effect of blending avocado seed starch and PLA was optimized using the RSM approach by using two variables: water absorption and biodegradability. Mixing them using RSM gave the best result: 1.8 g of starch and 3 g of PLA. Degradable plastic has a tensile strength of 10.1 MPa, elongation at a break of 85.8%, and a Young’s modulus of 190 MPa. Infrared spectroscopy showed that the plastic had a -OH bond at 3273.20 cm−1, 3502.73 cm−1, and 3647.39 cm−1, a CH2 bond at 2953.52 cm−1, 2945.30 cm−1, and 2902.87 cm−1, a C=C bond at 1631.78 cm−1, and a C-O bond at 1741.72 cm−1. The plastic decomposed in the soil. It was organic and hydrophilic. Thermal tests demonstrated that the plastic can withstand heat well, losing weight at 356.86 °C to 413.64 °C, forming crystals and plastic melts at 159.10 °C—the same as PLA. In the melt flow test, the sample melted before measurement, and was therefore not measurable—process conditions affected it. A water absorption of 5.763% and biodegradation rate of 37.988% were found when the samples were decomposed for 12 days. The starch and PLA fused in the morphology analysis to form a smooth surface. The RSM value was close to 1. The RSM gave the best process parameters.